Comprehensive analysis of the institutional landscape in Colombia: Examining the dynamics of Food, Land, and Water (FLW) arenas - Buritica, Alexander; Collazos Acosta, Sara Estefania; Pierce, Deborah; Castro, Augusto (2023)
This report will specifically focus on examining the intricate relationships among different stakeholders in Colombia's policy domains of food, water, and land. The emphasis will be on understanding the roles of various institutions and stake holders in these domains and their contributions to the policy process stages—design, implementation, and evaluation. The analysis aims to provide valuable insights into how these stakeholders interact within the institutional landscape, shedding light on the dynamics and effectiveness of policies shaping the realms of food, water, and land in Colombia.